Effects of acute creatine loading with or without carbohydrate on repeated bouts of maximal swimming in high-performance swimmers - Theodorou, A. S.; Havenetidis, K.; Zanker, C. L.; O'Hara, J. P.; King, F. G. J.; Hood, C.; Paradisis, G.; Cooke, C. B. (The Journal of Strength and Conditioning Research, 2005)
The addition of carbohydrate (CHO) to an acute creatine (Cr) loading regimen has been shown to increase muscle total creatine content significantly beyond that achieved through creatine loading alone. However, the potential ergogenic effects of combined Cr and CHO loading have not been assessed. The purpose of this study was to compare swimming performance, assessed as mean swimming velocity over repeated maximal intervals, in high-performance swimmers before and after an acute loading regimen of either creatine alone (Cr) or combined creatine and carbohydrate (Cr + CHO). Ten swimmers (mean ± SD of age and body mass: 17.8 ± 1.8 years and 72.3 ± 6.8 kg, respectively) of international caliber were recruited and were randomized to 1 of 2 groups. Each swimmer ingested five 5 g doses of creatine for 4 days, with the Cr + CHO group also ingesting 100 g of simple CHO 30 minutes after each dose of creatine. Performance was measured on 5 separate occasions: twice at "baseline" (prior to intervention, to assess the repeatability of the performance test), within 48 hours after intervention, and then 2 and 4 weeks later. All subjects swam faster after either dietary loading regimen (p < 0.01, both regimens); however, there was no difference in the extent of improvement of performance between groups. In addition, all swimmers continued to produce faster swim times for up to 4 weeks after intervention. Our findings suggest that no performance advantage was gained from the addition of carbohydrate to a creatine-loading regimen in these high-caliber swimmers.